Land Suitability and Carrying Capacity Analysis Of The Mangrove Ecotourism At Sarawet Village, East Likupang District, North Minahasa Regency - Tangkudung, Maureen J. N. N.; Schaduw, Joshian N. W.; Sondak, Calvyn F.A.; Wantasen, Adnan S.; Sumilat, Deiske A.; Rondonuwu, Arie B.; Luasunaung, Alfrets (Jurnal Ilmiah Platax, 2024)
The coastal area of Sarawet Village, East Likupang District, North Minahasa Regency, North Sulawesi Province has a mangrove forest covering an area of 379 hectares. Apart from being a living habitat for marine biota, this large area of mangrove is also an ecotourism destination. The purpose of this research is to determine the suitability of mangrove lands as ecotourism areas; Determine the ecological carrying capacity of the area for mangrove ecotourism activities; Assess public perceptions regarding the benefits of mangrove ecosystems and their potential to be developed as ecotourism destinations. The research method is a survey describing ecological, socioeconomic, institutional, and infrastructure conditions. Data collection is grouped into primary data and secondary data. Primary data collection was carried out through direct observation in the field by measuring the ecological potential of mangroves, visual observation of biota, and information from the community obtained directly at the research location through structured interviews with respondents. Based on the results of the study, the Tourism Suitability Index (IKW) value for the Sarawet Village mangroves was 2.73, which indicates the Very Suitable category for being developed as a mangrove river ecotourism area, as well as the public's perception of the benefits of the mangrove ecosystem and its potential to be developed as an ecotourism destination is very good. so it is hoped that this can improve the welfare of the existing community. Keywords: Mangroves, Ecotourism, Sarawet Abstrak Kawasan pesisir Desa Sarawet Kecamatan Likupang Timur Kabupaten Minahasa Utara Provinsi Sulawesi Utara memiliki hutan mangrove seluas 379 hektar, keberadaan mangrove yang luas ini selain menjadi habitat hidup bagi biota laut juga sebagai tujuan ekowisata. Tujuan dan manfaat penelitian ini adalah menentukan kesesuaian lahan mangrove sebagai kawasan ekowisata; Menentukan daya dukung ekologis kawasan untuk kegiatan wisata mangrove ekowisata; Mengkaji persepsi masyarakat tentang manfaat ekosistem mangrove dan potensinya untuk dikembangkan sebagai tujuan ekowisata. Metode penelitian yang digunakan yaitu melakukan survei untuk mendeskripsikan kondisi ekologi, sosial ekonomi, kelembagaan dan infrastruktur. Pengumpulan data dikelompokkan menjadi data primer dan data sekunder. Pengumpulan data primer dilaksanakan melalui pengamatan langsung di lapangan dengan melakukan pengukuran potensi ekologi mangrove, pengamatan biota secara visual dan informasi dari masyarakat diperoleh langsung di lokasi penelitian melalui wawancara secara terstruktur dengan responden. Berdasarkan hasil kajian diperoleh nilai Indeks Kesesuaian Wisata (IKW) mangrove Desa Sarawet yakni sebesar 2,73 yang menunjukkan kategori Sangat Sesuai untuk dapat dikembangkan sebagai Kawasan ekowisata sungai mangrove, serta persepsi masyarakat tentang manfaat ekosistem mangrove dan potensinya untuk dikembangkan sebagai tujuan ekowisata adalah sangat baik sehingga diharapkan hal tersebut dapat meningkatkan kesejahteraan masyarakat yang ada. Kata Kunci : Mangrove, Ekowisata, Sarawet